2022
DOI: 10.1002/hsr2.730
|View full text |Cite
|
Sign up to set email alerts
|

Licensure and citations among nail salons in Michigan from 2017 to 2021: A cross‐sectional study of an overlooked and vulnerable industry

Abstract: Background: Nail salon workers (NSW) in the United States (U.S.) are predominantly immigrant women who face a number of occupational hazards, such as biological, ergonomic, and chronic chemical exposures. Additionally, there are challenges to keeping up with the latest practices in this evolving small business industry.Licensure requirements are intended to keep not only consumers but also workers safe, however licensure requirements vary between states creating little skill, education, and occupational health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 19 publications
0
1
0
Order By: Relevance
“…For example, Quach et al [ 18 ] showed that salon workers who were trained demonstrated improved knowledge of safety precautions in salons and were more likely to use protective measures such as use of protective clothing. In the State of Michigan, for instance, Le et al [ 19 ] found evidence that suggested the need for continuing education for nail salon workers. However, the knowledge base of salon workers in countries such as Kenya that lack national guidelines on both occupational safety for salon workers and mandatory training is unavailable.…”
Section: Introductionmentioning
confidence: 99%
“…For example, Quach et al [ 18 ] showed that salon workers who were trained demonstrated improved knowledge of safety precautions in salons and were more likely to use protective measures such as use of protective clothing. In the State of Michigan, for instance, Le et al [ 19 ] found evidence that suggested the need for continuing education for nail salon workers. However, the knowledge base of salon workers in countries such as Kenya that lack national guidelines on both occupational safety for salon workers and mandatory training is unavailable.…”
Section: Introductionmentioning
confidence: 99%